A new species of Thyreus from northern Cameroon (Hymenoptera: Apidae) - Engel, Michael S. (Journal of Melittology, 2014)
A new species of the cleptoparasitic bee genus Thyreus Panzer (Apinae: Melectini) is described and figured from two females captured near Garoua in northern Cameroon.  Thyreus garouensis Engel, new species, is distinguished from other African Thyreus with pallid pastel blue pubescence.  The species is most similar to T. scotaspis (Vachal), but can be distinguished on the basis of its pattern of coloration/pubescence and form of the mesoscutellum.